Resilience in the face of sexual minority stress: "Choices" between authenticity and self-determination. Issue 1 (2nd January 2016) - Levitt, Heidi M.; Horne, Sharon G.; Herbitter, Cara; Ippolito, Maria; Reeves, Teresa; Baggett, Linda R.; Maxwell, David; Dunnavant, Bridget; Geiss, Meghan
ABSTRACT: This qualitative study explored the experience of sexual minority stressors and corresponding resilience. Using a grounded theory approach, the core category identified in the analysis was minority stress results from systemic factors that cause lesbian, gay, and bisexual (LGB) people to face competition between their desires for authenticity and self-determination . These findings shed light upon the insidious nature of minority stress, especially within U.S. contexts that lack protective legislation, and the adaptive strategies people use to mitigate their effects. By positioning resilience as a choice between authenticity and self-determination, resilience is understood to lessen but not resolve the deleterious impact of sexual minority stress.